EFFECT OF GY LEAF SPOT ON OIL CONTENT OF RAPESEED AND MUSTARD: Short Communication - Shah, SJawad Ahmad; Ali, Iftikhar (Biological Sciences - PJSIR, 2002)
Grey leaf spot (GLS) is an economically important fungal disease of rapeseed and mustard in many parts of the world. Alternaria brassicae (Berk.) sacc. the causal agent of GLS is a necrotrophic pathogen and can produce conspicuous spotting of all aerial plant parts depending on the host reaction and environmental conditions (Kolte 1985 and Conn et al 1990). There are conflicting reports on the effect of A.brassicae on the oil content of Bras sica spp. seeds (Stovold et al1987 and Seidle et aI1995). The present study was therefore undertaken to examine this conflicting and unaddressed problems of rapeseed and mustard in Pakistan due to severe edible oil crises in the country.